Assessing Accountability in Practice: The Asian Development Bank's Accountability Mechanism. Issue 4 (21st November 2015) - Park, Susan
Abstract: Intergovernmental Organizations (IOs) such as the Asian Development Bank (ADB) were created by and for states. The ADB was established to further economic growth and cooperation in the Asia Pacific. At the behest of its powerful member states the ADB created an accountability mechanism (AM) in 1995. This mechanism was created to provide recourse to people that might be or are 'directly materially and adversely affected' by a development project financed by the ADB. As with the other Multilateral Development Banks (MDBs), the creation of such an 'external accountability mechanism' recognized a legally relevant relationship between an IO and private persons. This article investigates the operations of the ADB's AM. Arguably, the ADB's AM has brought some improvement to affected people through its mediation, compliance investigations and monitoring. Yet analysis of the mechanism also demonstrates that progress is hampered by a lack of access, transparency, Developing Member Country (DMC) resistance, staff obstruction and a lack of independence in the mechanism itself. Abstract : Powerful member states demanded the ADB create an external accountability mechanism. This mechanism provides recourse to people that are or might be 'directly materially and adversely affected' by a development project financed by the ADB.